Voices behind the left shoulder: Two patients with right-sided temporal lobe epilepsy - Hug, Andreas; Bartsch, Andreas; Gutschalk, Alexander (Journal of the neurological sciences, 2011)
Auditory vocal hallucinations are sometimes observed in temporal-lobe epilepsy, but are a frequent sign of psychosis and may rarely be mistaken for the latter. Here we report two patients who suffered from auditory vocal hallucinations, described as unintelligible human voices perceived at their left side during epileptic seizures. MEG revealed interictal epileptic discharges within the anterior partition of the right superior temporal gyrus; signal-to-noise ratio of these discharges was overall poor in EEG. The findings suggest that auditory vocal hallucinations without verbal content can evolve in the right hemisphere and are probably independent of language lateralization. This is in accordance with evidence from functional imaging, whereas most previous reports of seizures with auditory vocal hallucinations were confined to the left hemisphere.
Gesehen am 01.07.2022